The effect of shadow training using a racket and shadow training using a shuttlecock on the agility improvement of athletes in badminton - Zaidan, Agil Gusti; Pitriani, Pipit; Tafaqur, Muhamad (Jorpres (Jurnal Olahraga Prestasi), 2024)
Agility is the ability to move to change direction quickly without losing balance. This study aims to determine the ef ect of shadow training methods using rackets and shadow training using shuttle cock on increasing the agility of UPI Badminton UKM athletes. The method used in this research is an experimental method using A Group Pre-test and Post-Test Design. The population in this study were all UPI badminton UKM athletes totaling 32 people, the sample used a purposive sampling technique of as many as 12 people. The data collection technique was carried out by giving an initial test to 2 groups. Then given treatment with the shadow training method using a shuttle cock and shadow training using a racket, then given a final test using the shadow 2 return test. Data processing techniques were carried out with descriptive statistical analysis and paired t-tests. Both shadow training methods influence increasing agility, but the shadow training method using shuttle cock has a more significant influence. So it can be concluded that the shadow training method using shuttle cock has a more significant ef ect on increasing the agility of UPI Badminton UKM athletes.